LAMPU TIDUR OTOMATIS MENGGUNAKAN SENSOR LDR BERBASIS ARDUINO UNO - Susanta, Muhamad Hilmansyah (LPPM Politeknik Pajajaran ICB Bandung, 2024)
The use of switches to turn on and turn off the electricity of lights is commonly used in everyday life. It is used in several installations covering rooms including garden lights, room lights, terrace lights and warehouse lights. Night lights are used to help sleep more soundly. The light intensity produced by night lights is very dim so it does not disturb you when sleeping. In making this tool, the lights automatically turn on and off the sleeping lights so that the user does not need to press the on and off switch to turn them on and off. Some of the equipment includes an LDR sensor as input which is used to detect the presence of light, a relay which is used as an output to disconnect and connect the PLN electricity supply, an Arduino Uno microcontroller which functions as an input and output data processor.